The Monumental Inscriptions from Early Islamic Iran and Transoxiana - Blair, Sheila S., (Middle East and Islamic Studies - Book Archive pre-2000., 1991)
Inscriptions on buildings are a distinctive feature of Islamic architecture, and this book studies the 79 surviving monumental inscriptions in the Iranian world from the first five centuries of the Muslim era (A.D. 622-1106), the period in which all the major trends of monumental epigraphy in the area were set. These foundation, commemorative, and funerary texts come from the region between Iraq and Soviet Central Asia. Written primarily in Arabic, they embellished architectural monuments and furnishings whose nature implies the construction of major buildings. An extended introduction discusses such general topics as titulature, patronage, and stylistic development. Each text is then presented individually with photographs, drawings, transcriptions, translations and an extensive commentary, which presents the inscription in its larger palaeographic and historical contexts.